Merging Worlds: Place, Politics, and Play in Martin McDonagh’s The Pillowman - Haughton, Miriam (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Martin McDonagh’s transition from his regional Leenane Trilogy (1996-1997) and Aran Island plays (1996-2001) to The Pillowman (2003) marks a significant departure in his dramaturgical approach. The absence of a specified geographical location in The Pillowman challenges traditional notions of place in theatre. While space is fundamental in constructing meaning, Anne Ubersfeld suggests that plays offer socio-cultural coordinates rather than literal representations. In The Pillowman, McDonagh explores power dynamics within an unspecified totalitarian state, highlighting the tensions between official authority and individual agency. Thus, while the play lacks a specific dramatic locale, the politics of place still shape the narrative and character interactions.